The New Soviet Man With a Female Body: Mother, Teacher, Tractor Driver… - Kestere, Iveta; Stonkuviene, Irena; Rubene, Zanda (Acta Paedagogica Vilnensia, 2020)
The “New Man” is a utopian concept that involves creating an ideal man and replacing the imperfect human being. The beginning of the ideas of creating the new man can be found in ancient Greece and Rome, in the works of utopians and educators, as well as in theological texts. Although this ideologeme as one of the constructs of modernity was fully formed by the end of the 19th century, the efforts to practically implement it are connected with the establishment of (para)totalitarianism. One of the best-known examples of such an attempt was the ambition to create the New Soviet Man. After giving up aspirations to create a perfect biological individual, in the long-term perfective, the main focus was laid on forming an ideologically correct New Man, a builder of communism. Education was seen as one of the key means of achieving this objective. Seeking to identify how the image of the New Man was reflected in the curriculum (primary in particular), 36 textbooks published between 1925–1985 and used in the state schools of Soviet Russia and the Baltic States were analysed.Although the concept of the New Man includes both the male and female person, the most frequently considered is a male. This article aims to discuss how textbooks represent the Soviet woman by considering the following aspects: what was specific to the New Soviet Man – Woman? What did the Soviet regime expect from women in the context of the New Soviet Man project? How did the project of New Man reflect the gender equality idea?
Keywords: Soviet education; New Man; Soviet woman; gender equality; textbooks